2023
DOI: 10.3390/ijms24043084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Berries, Phytochemicals, and Probiotics on Atherosclerosis through Gut Microbiota Modification: A Meta-Analysis of Animal Studies

Abstract: Atherosclerosis is a major cause of death and disability. The beneficial effects of phytochemicals and probiotics on atherosclerosis have gained significant interest since these functional foods can improve inflammation, oxidative stress, and microbiome dysbiosis. The direct effect of the microbiome in atherosclerosis, however, needs further elucidation. The objective of this work was to investigate the effects of polyphenols, alkaloids, and probiotics on atherosclerosis using a meta-analysis of studies with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…A metagenome-wide association study on stools from 218 individuals with atherosclerotic cardiovascular disease showed that their gut microbiomes showed increased abundances of Enterobacteriaceae and Streptococcus spp., differently from 187 healthy controls, concluding that the gut microbiota could play a role in cardiovascular diseases [79]. What is more, consumption of functional foods rich in phytochemicals as well as probiotics are feasible interventions to ameliorate gut health and reduce plaque burden in patients suffering from cardiovascular disease [80]. The previous finding could have an important clinical aspect.…”
Section: Discussionmentioning
confidence: 97%
“…A metagenome-wide association study on stools from 218 individuals with atherosclerotic cardiovascular disease showed that their gut microbiomes showed increased abundances of Enterobacteriaceae and Streptococcus spp., differently from 187 healthy controls, concluding that the gut microbiota could play a role in cardiovascular diseases [79]. What is more, consumption of functional foods rich in phytochemicals as well as probiotics are feasible interventions to ameliorate gut health and reduce plaque burden in patients suffering from cardiovascular disease [80]. The previous finding could have an important clinical aspect.…”
Section: Discussionmentioning
confidence: 97%
“…Low alpha diversity is often used as a characteristic to evaluate dyslipidemia [ 59 ]. The increase of F/B ratio accelerated the accumulation of lipids and alters the production of SCFAs, which is a predictor of metabolic diseases [ 60 , 61 ]. Rb1 intervention upregulated the abundance of Lactobacillus, Prevotella and Bacteroides in AS rats.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, supplementation of rodents with Akkermansia muciniphila has resulted in an amelioration of the increased TMAO levels and blood pressure as well. It is noteworthy that Depommier et al in their landmark study among humans have demonstrated that supplementation with this NGP has been a safe and well-tolerated method to improve parameters of the metabolic syndrome among overweight/obese patients [ 76 ].…”
Section: The Role Of Dietary Choline In Cardiometabolic Disordersmentioning
confidence: 99%